Defining Christianity and Judaism from the Perspective of Religious Anarchy - Magid, Shaʾul (The journal of Jewish thought & philosophy, 2017)
This essay explores Martin Buber’s rendering of Jesus and the Ba‘al Shem Tov as two exemplars of religious anarchism that create a lens through which to see the symmetry between Judaism and Christianity. The essay argues that Buber’s use of Jesus to construct his view of the Ba‘al Shem Tov enables us to revisit the “parting of the ways” between Judaism and Christianity through the category of the religious anarchist.